1999
DOI: 10.1007/s10434-999-0350-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Embolization for the Treatment of Misperfusion After Hepatic Artery Chemoinfusion Pump Implantation

Abstract: Transcatheter coil embolization is the therapy of choice for the management of hepatic artery chemoinfusion pump misperfusion. It is rapid, effective, and well tolerated by patients and obviates the need for additional surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Nuclear medicine physicians are required to conduct and interpret nuclear scintigraphy studies to ensure that extrahepatic perfusion is avoided. When extrahepatic perfusion is detected or when catheter-related complications occur, treatment can be salvaged with advanced interventional radiology techniques 33,34 . Finally, given the complexity of the care coordination and the frequency of tests and treatment in patients receiving haip therapy, dedicated nursing support is paramount to support a haip program.…”
Section: Institutional Requirements For Haip Therapymentioning
confidence: 99%
“…Nuclear medicine physicians are required to conduct and interpret nuclear scintigraphy studies to ensure that extrahepatic perfusion is avoided. When extrahepatic perfusion is detected or when catheter-related complications occur, treatment can be salvaged with advanced interventional radiology techniques 33,34 . Finally, given the complexity of the care coordination and the frequency of tests and treatment in patients receiving haip therapy, dedicated nursing support is paramount to support a haip program.…”
Section: Institutional Requirements For Haip Therapymentioning
confidence: 99%
“…2) and to rule out any arteriovenous shunting. Extrahepatic perfusion should be confirmed with an arteriogram, and the culprit vessel should be embolized, if possible [27]. Early pump-related complications are uncommon (5%-10%) and usually technically related, including hepatic artery thrombosis, pump pocket hematomas, wound infections, underperfusion of liver, and/or extrahepatic perfusion.…”
Section: Pump Placementmentioning
confidence: 99%
“…Bloom et al [14] reported 16 patients with liver metastasis from colorectal carcinoma and HAIC misperfusion. They separated the patients in two groups, extrahepatic (n=8) and intrahepatic (n=8) misperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Gastroduodenal endoscopy allows the distribution of the ulcers in the territories of the misperfused arteries to be confirmed. The use of methylene blue administration via the arterial port during endoscopy has been used to establish gastroduodenal misperfusion from HAIC [13,14]. Gastroduodenal abnormalities ranged from typical benign ulcers to a pattern of epithelial atypia and multiple ulcerations that may be falsely considered malignant [6].…”
Section: Discussionmentioning
confidence: 99%